Distribution of Diurnal Bird in Pine Forests and Citrus Orchard in Bedengan, Selorejo Village, Malang - Polii, Oky A.I.; Yanuwiadi, Bagyo (Proceeding International Conference on Global Resource Conservation, 2015)
Selorejo village located in the district of Dau, Malang regency, is a village that has a lot of potential for nature tourism. Selorejo village in the region of Malang the north, to the village of Ivory Kulon as boundary north, Tegalweru village as the East boundary, and the boundary south is the Petung Sewu village. One potential place for tourism is Bedengan. A location which has a camping ground yet around the site are some kind variety of vegetation types like pine forests and citrus groves dominated by local residents.. The purpose of this research is to determine distribution spatial and temporal diurnal birds in Bedengan and to found bird in citrus orchards and pine forests. This research was conducted in May-October 2015. The Methods is the point count method that have been modified, the method of observation the birds. and data analysis include F (frequency), K (Density), FR (Relative Frequencies), KR (Relative Density), Important Value Index (IVI), temporal using Microsoft Office Excel 2007 software and Spatial design of birds using Photoshop. From the results obtained, At pine forest land is dominated by Glossy swiftlet (Collocalia esculenta). On citrus orchard land dominated by Sooty-headed bulbul (Pycnonotus aurigaster). some birds in pine forests often conducting activities in the air like a Glossy swiftlet (Collocalia esculenta). Heading like Spotted dove (Streptopelia chinensis), sooty-headed bulbul (Pycnonotus aurigaster), Rusty-breasted cuckoo (Cacomantis sepulcralis). At branching like Olive-backed tailorbird (Orthotomus sepium). Javan kingfisher (Halcyon cyanoventris), Eurasian tree sparrow (Passer montanus). Whereas birds in the orange orchard did activity in the Air like Glossy swiftlet (Collocalia esculenta). On Heading like sooty-headed bulbul (Pycnonotus aurigaster) and Eurasian tree sparrow (Passer montanus). The results showed that on the morning the dominate in citrus orchard is Glossy swiftlet followed by the Sooty-headed bulbul and Javan kingfisher while the pine forest is Sooty-headed bulbul followed by Glossy swiftlet and the Eurasian tree sparrow. At noon that dominate in orange orchard is Glossy swiftlet followed by the Sooty-headed bulbul and Spotted dove while the pine forests dominates by the Sooty-headed bulbul followed by Glossy swiftlet and Olive-backed tailorbird. In the afternoon which dominates the citrus orchard is Glossy swiftlet while the dominate in pine forest is Glossy swiftlet followed by Javan kingfisher and Sooty-headed bulbul.Keywords: Distribution; diurnal bird; Bedengan